The Implementation of Peer Feedback to Improve Writing Skills of the Eleventh Grade Students of SMA Negeri 1 Bungku Tengah - Oli’i, Apriliani; Budi, Budi; Lebagi, Desrin; Rofiqoh, Rofiqoh; Putri, Dwi (Journal of English Language and Education, 2025)
The aim of this research was to prove whether implementation of Peer Feedback effectively improve students’ writing skill. This study employed a quasi-experimental design. The population involved all eleventh-grade students at SMA Negeri 1 Bungku Tengah, totaling 277 learners. To determine the Experimental and Control groups, the researcher used cluster random sampling. The researcher used a descriptive text writing test to collect data in terms of pretest and posttest. However, only the experimental class received peer feedback treatment while the control group received other treatments. Organization, Content, vocabulary, grammar, and mechanics were the focus of this study. The results demonstrated that once peer feedback was introduced, the experimental group outperformed the control group on the post-test, with a mean score of 76.12 compared to 61.78. Meanwhile, analysis of the pre-test indicated that there was no statistically significant difference between the two groups’ average scores. In addition, the obtained significance value (2-tailed) was 0.001, which is lower than the standard level of 0.05. This suggests that the use of peer feedback has a statistically significant and meaningful effect on improving students’ writing skill. Consequently, peer feedback can be considered an advisable strategy for writing instruction.